Subcutaneous daratumumab and hyaluronidase-fihj in newly diagnosed or relapsed/refractory multiple myeloma. (January 2021) - Sanchez, Larysa; Richter, Joshua; Cho, Hearn Jay; Jagannath, Sundar; Madduri, Deepu; Parekh, Samir; Richard, Shambavi; Tam, Lowena; Verina, Daniel; Chari, Ajai
Daratumumab, a human immunoglobulin G1 kappa monoclonal antibody that targets CD38, is currently approved as monotherapy and in varying combinations with approved anti-myeloma regimens in both newly diagnosed multiple myeloma and relapsed refractory multiple myeloma. Originally developed for intravenous administration, the subcutaneous formulation of daratumumab (daratumumab and hyaluronidase-fihj) was recently approved by the US Federal Drug Administration and European Commission in 2020. In clinical trials, compared with the intravenous formulation, subcutaneous daratumumab (Dara-SC) has significantly shorter administration time (median first dose 7 h versus 3–5 min, respectively), lower rates of infusion-related reactions (median first dose 50% versus less than 10%, respectively), and lower volume of infusion (median 500–1000 ml versus 15 ml, respectively). Otherwise, the pharmacokinetics, safety profile, and efficacy are comparable. This review summarizes the pivotal trials that led to the approval of Dara-SC, highlights important clinical considerations for the use of Dara-SC, and provides practical guidelines for the administration of Dara-SC in the clinic.